Breakthrough Thinking for Nonprofit Organizations - Bernard Ross, Clare Segal (Jossey-Bass, 2002)
This book is for managers and board members in nonprofit organizations. It’s designed to provide an ideas toolbox for those individuals who want to achieve significant—maybe even breakthrough —change in their organizations, whether that change is in fundraising, service delivery, or all-around performance. We use the toolbox metaphor because we’ve written the book specifically so you can pick and choose the tools or techniques that work best for you. Bear in mind, though, that some tools are a great deal easier to learn to use than others. Remember too that a toolbox isn’t a set of instructions— you still need to have a plan! The book has mostly arisen out of our consulting and training work with nongovernmental organizations (NGOs) and nonprofits worldwide, especially in Europe, the United States, South America, and Africa. Our company, =MC, is an international consultancy and management training organization. We work exclusively with nonprofit organizations, and our customers include many of the world’s largest and most challenging nonprofits, including UNAIDS, UNHCR, Greenpeace International, Amnesty International, and the International Federation of the Red Cross and Red Crescent. We’ve also carried out assignments for organizations as diverse as the President’s Office in Egypt, the Tate Gallery in London, the UK Labour Party, and the Council on Foundations in the United States. In this book, we aim to provide enough exercises and examples of both disasters and best practice for you to assess how you might avoid the mistakes of others and apply their successes in your organization. Most examples are from nonprofits. Some, though, are drawn from the private sector because they show best practice in our view. The key thing is to be open to learning from whatever quarter it comes. What we’re not trying to do is provide a step-by-step, how-to guide to achieving breakthrough. Methods and approaches will differ depending on who you are, on the type of organization you run, and how far you are (or are not) into the process. There is no one way to do it, and the nature of transformations is that they are messy and hard to predict or even manage. Many such efforts inevitably fail in absolute terms. But even in that effort there is great learning. (We’d love to hear more from you; please send examples of your successes and, yes, failures. You can contact us at www.managementcentre. co.uk.)